Návrh projektu a aplikace metodiky projektového managementu v podniku - Zvolenská, Dominika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2018)
Diplomová práca je zameraná na návrh projektu hackathonu a aplikáciu metód projektového managementu vo vybranej firme. Úvodná časť sa zaoberá teoretickými východiskami z oblasti projektového riadenia, v druhej časti je následne vykonaná analýza súčasného stavu firmy. Výstupom a treťou časťou práce je venovaná samotnému návrhu projektu.

The master thesis focuses on the project design of hackathon and application of project management methods in the selected company. The first part is devoted to theoretical background in the area of project management, the second part contains the analysis of the current situation in the company. The output and third part of the thesis is devoted to the project itself.
Project Proposal and the Application of the Project Management Methods in a Company
Keywords: projektový management; projekt; hackathon; časový plán; riziko; náklady; analýza; project management; project; hackathon; time schedule; risk; costs; analysis